Meningkatkan Kemampuan Mengenal Lambang Bilangan Dengan Bermain Kartu Angka Pada Anak Tunagrahita Ringan di Slb-C Katolik Santa Anna Tomohon - Dapa, Aldjon Nixon; Marentek, L.K.M; Ruron, Maria Valeria Nogo (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to improve the ability to recognize number symbols in mildly mentally retarded children in grade VII at SLB-C Katolik Santa Anna Tomohon by playing number cards. The research method used is SSR (Single Subject Research) with an A-B-A research design. A1 (Baseline-1) is the initial test before the subject receives intervention, B (Intervention) is the condition of the subject when receiving treatment and A2 (Baseline-2) is the final test of the subject after receiving intervention. In this study, data collection techniques were through observation and interviews with teachers and principals. The results of the study can be proven that the research subjects increased. Where in baseline-1 before being given treatment, the percentage was 25%, in the intervention phase 75% and baseline-2 got satisfactory results of 83.33%. The change in the means value obtained at baseline-1 only reached 0.75 and at baseline-2 showed the means level obtained was 2.5 and the change in data level between conditions at Intervention/baseline-2 was (+2) and at baseline-2/intervention conditions was (+3) indicating a good trend and there was no overlapping data because the percentage was 0% indicating no overlapping data. From the results of this study, it can be concluded that the use of number card media is effective in improving the ability to recognize number symbols in children with mild mental retardation. This study is expected to contribute to other researchers who are interested in studying the same problem, as well as providing guidance in developing more effective interventions to support the education of children with mental retardation. The results showed that playing number cards can help mildly disabled children to recognize number symbols. In addition, the use of media encourages the creation of a more adaptable and inclusive curriculum. Educators should be trained in the use of new learning media that can improve the academic abilities of mildly retarded students. This has a theoretical basis that supports the learning approach of using concrete media in the education of children with special needs. This approach is in line with constructivist learning theory which emphasizes the importance of direct experience in the learning process. Therefore, playing number cards helps education practically and theoretically. Games are also the theoretical basis for inclusive education